Analysis on Status of Developing Low Carbon Economy and Selection of Evaluation Index in China (Global Journal of Management and Business Research, 2012)
With the process of industrialization and urbanization accelerating, climate warming caused by CO2 produced by lots of fossil fuels consumption has been more and more serious, so developing low carbon economy has become a new economic model. Based on historical data and the background of low carbon economy, this paper firstly expounds the status of China#x2019;s low carbon economy and secondly sums up existing problems according to the actual situation and gives a basic model of developing low carbon economy in China. Finally, this paper establishes an index system of evaluating the comprehensive level of low carbon economy according to the status of China#x2019;s low carbon economy and the principles of selecting index.
Keywords: China; low carbon economy; status and development model; selection of evaluation index